DISKURSUS KEARIFAN LOKAL UNTUK PENGEMBANGAN CITY BRANDING MAGELANG KOTA SEJUTA BUNGA - Galih Putra Pamungkas; Achmad Sultoni (LPPM Institut Bisnis dan Teknologi Indonesia, 2020)
This research is a discourse to streamline the development of the city branding concept of Magelang City of One Million Flowers by exploring the potential of local wisdom owned by the City of Magelang. Currently, the City of Magelang has the slogan